2016
DOI: 10.1103/physrevb.93.094525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Van Hove singularities on high- Tc superconductivity in H3S

Abstract: One of interesting open questions for the high transition temperature (Tc) superconductivity in sulfur hydrides is why high pressure phases of H3S have extremely high Tc's. Recently, it has been pointed out that the presence of the van Hove singularities (vHs) around the Fermi level is crucial. However, while there have been quantitative estimates of Tc based on the Migdal-Eliashberg theory, the energy dependence of the density of states (DOS) has been neglected to simplify the Eliashberg equation. In this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
123
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 92 publications
(164 reference statements)
14
123
0
Order By: Relevance
“…1) are known to give low T c values [9,13,17], which agree relatively well with the experimental values with the low-T annealing for the low-pressure regime. Im3m-H 3 S (Fig.…”
Section: Fig 1: Experimentally Observedsupporting
confidence: 83%
See 1 more Smart Citation
“…1) are known to give low T c values [9,13,17], which agree relatively well with the experimental values with the low-T annealing for the low-pressure regime. Im3m-H 3 S (Fig.…”
Section: Fig 1: Experimentally Observedsupporting
confidence: 83%
“…Im3m-H 3 S (Fig. 1) has been thought to give the T c with the high-T annealing cases [11,14,15,17,[21][22][23][24][25][26][27][28][29][30][31], and its presence is recently confirmed with the X-ray diffraction measurements [8,18,32,33] The P1 and Cmca structures can now be distinguished by the configuration of the inter-unit bonding. The uniform (alternating) bonding orientation yields the P1 (Cmca) structure.…”
Section: Fig 1: Experimentally Observedmentioning
confidence: 96%
“…Potential applications of the sparse sampling scheme include state-of-the-art methods for strongly correlated materials such as GW +DMFT [32][33][34][35][36] and the selfenergy embedding theory (SEET) [41]. Quantitative estimates of superconducting temperature T c based on the Migdal-Eliashberg theory in ab initio calculations may benefit from the sparse sampling scheme so that the constant density of states approximation is no longer necessary [63].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies, which have shown that the superconductivity observed in Ref. [38] arises primarily from an H 3 S phase [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] whose structure has been recently confirmed experimentally [56], will not be described within this short review. We will, however, discuss the results of first principles calculations carried out for the hydrides of phosphorus [57][58][59].…”
Section: Introductionmentioning
confidence: 99%